The Princeton field guide to dinosaurs - Paul, Gregory S. (Princeton field guides., 2016)
The best-selling Princeton Field Guide to Dinosaurs remains the must-have book for anyone who loves dinosaurs, from amateur enthusiasts to professional paleontologists. Now extensively revised and expanded, this dazzlingly illustrated large-format edition features some 100 new dinosaur species and 200 new and updated illustrations, bringing readers up to the minute on the latest discoveries and research that are radically transforming what we know about dinosaurs and their world. Written and illustrated by acclaimed dinosaur expert Gregory Paul, this stunningly beautiful book includes detailed species accounts of all the major dinosaur groups as well as nearly 700 color and black-and-white images--skeletal drawings, "life" studies, scenic views, and other illustrations that depict the full range of dinosaurs, from small feathered creatures to whale-sized supersauropods. Paul's extensively revised introduction delves into dinosaur history and biology, the extinction of nonavian dinosaurs, the origin of birds, and the history of dinosaur paleontology, as well as giving a taste of what it might be like to travel back in time to the era when dinosaurs roamed the earth. Now extensively revised and expandedCovers nearly 750 dinosaur species, including scores of newly discovered onesProvides startling new perspectives on the famed Brontosaurus and TyrannosaurusFeatures nearly 700 color and black-and-white drawings and figures, including life studies, scenic views, and skull and muscle drawingsIncludes color paleo-distribution maps and a color time lineDescribes anatomy, physiology, locomotion, reproduction, and growth of dinosaurs, as well as the origin of birds and the extinction of nonavian dinosaurs